Efektivitas Pengelolaan Keuangan pada Rumah Makan Lontong Blora di Karangjati, Kabupaten Semarang - Dao, Adikaria; Maria Th, Alleta Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to analyze the financial management at Rumah Makan Lontong Blora in Karangjati, Semarang Regency. The focus of the research is on the challenges faced by the owner in accounting and taxation management. To address this issue, financial management and accounting theories for SMEs are used as references. Data were collected through in-depth interviews with the owner and direct observations of the financial management practices implemented. The analysis results indicate that the financial management is still simple, with deficiencies in understanding accounting and tax obligations. Although the owner is aware of the need for improvement, there is a requirement for concrete steps, such as attending accounting training and tax consulting to enhance compliance. The owner also plans to utilize user-friendly financial applications that have relevant features for SMEs, such as automated financial reporting and inventory management. This study concludes that increasing knowledge about financial management and taxation is crucial for business sustainability. The research also contributes to the theory of financial management in SMEs by demonstrating the importance of implementing good financial practices to improve efficiency and performance in the culinary business.